LANSKAP ARKEOLOGI DALAM PERSPEKTIF PROSESUAL DAN PASCA-PROSESUAL: STUDI KASUS KOMPLEKS MEGALITIK DI DATARAN TINGGI JAMBI - Hafiful Hadi Sunliensyar (BRIN, 2018)
Abstract The development of archaeology paradigm from processual to postprocessual, influence the archaeologists thought about landscape. Sometimes, the landscape in archaeology is arduous understood because overlapping with other studies. Actually, this problem can be solved if we analyze the development of archaeology paradigm which associated with landscape study. This article attempts to discuss the ambiguity of landscape in archaeology with case study on the megalithic complex in Jambi Highland. Based on the data, it is known that: landscape in procesual study just explain the association between megalithic with burial-jars, mountains, settlements, and natural resources around it. The result which obtained in this perspective, was an explanation of megalithic function based on the relationship between sites and environment. Conversely in post-processual, attempts to interpret about megalithic complex in Jambi Higland based on individual (including researcher perception) or community perceptions. The result obtained in postprocessual, can answer questions about the unevenness of megalithic orientation and the difference of megalithic locations.